Hydrothermal carbonisation of cotton and polyester clothing waste for hydrochar and terephthalic acid production - Leung, Wai Hon (2025)
In the UK around 93,000 tonnes of clothing waste, which typically contain 55 % cotton and 23 % polyester, are sent to landfill every year. Under the European Green Deal, polyester terephthalate (PET) manufacturers are under pressure to increase recycling rates to 30 % by 2030. Therefore, this study focusses on using hydrothermal carbonisation (HTC) to produce terephthalic acid from both coloured PET and clothing waste containing dyes. The purity of terephthalic acid is important for recycling and typically needs to be over 99 % without measurable colour for manufacturing recycled plastic. Therefore, the specific aim for this study is to purify terephthalic acid from coloured PET bottles and polyester-containing clothing waste and, for the latter, to produce a hydrochar co-product that can be used as a solid hydrochar.